An Application of the What Works Clearinghouse Standards for Evaluating Single-Subject Research: Synthesis of the Self-Management Literature Base. (January 2013) - Maggin, Daniel M.; Briesch, Amy M.; Chafouleas, Sandra M.
The use of single-subject research in the development and evaluation of academic, psychological, and behavioral interventions has led to the experimental validation of an array of treatment options for a diverse set of educational challenges. However, the synthesis of these bodies of research has been the subject of considerable debate. In an effort to utilize the findings from studies using single-subject methodologies to identify effective educational practices, the What Works Clearinghouse developed a set of criteria to evaluate the strength of evidence for various strategies. In this article, an application of these standards is demonstrated using a body of self-management intervention studies drawn from a recently published systematic review. The utility of the standards for identifying evidence-based practices validated with single-subject research methods is discussed. In addition, a comparison of the What Works Clearinghouse procedures to previously developed methods for identifying evidence-based practices with single-subject research is provided, and implications for research and practice are described.